The influence of transformational leadership style and organizational culture during the Covid-19 pandemic on employee performance (Case Study at PT. Saung Berdikari Sentosa) - Siti Mida Isnaini; Muhammad Taufiq Amir (Sean Institute, 2024)
The purpose of this study was to analyze the influence between transformational leadership style and organizational culture on employee performance. The research method used by researchers is a quantitative data method using a survey given to respondents using a saturated sample of 100 people which is then processed using SPSS 25.0. The results of the research conducted show that there is a positive influence between transformational leadership style on organizational culture at PT. Saung Berdikari Sentosa with a significance value of 0.000 < 0.05. There is no influence between transformational leadership style on employee performance at PT. Saung Berdikari Sentosa with a significance value of 0.256 > 0.05. There is an influence between organizational culture on employee performance at PT. Saung Berdikari Sentosa. With a significance value of 0.02 < 0.05. There is a simultaneous influence between the transformational leadership style of organizational culture on employee performance at PT. Saung Berdikari Sentosa. Where the variables of transformational leadership style and organizational culture are able to influence financial performance variables by 87.2%.